Penerapan Hukum Kontrak dan Itikad Baik dalam Kerjasama Endorsement Antara Online Shop dan Selebritas Instagram - Jesica Septi Leony Simanungkalit; Cindy Eleonora Sitohang; Jesika Jesika; Dwie Belcha Nanda; Bonaraja Purba (CV. Ulil Albab Corp, 2024)
This research aims to examine the application of contract law and good faith in endorsement collaborations between online shops and Instagram celebrities. This research was conducted using a research method in the form of normative legal research. Normative legal research, also known as doctrinal research, involves the use of primary and secondary legal materials. These legal materials are systematically organized, analyzed, and then conclusions are drawn relating to the problems studied. Based on the research results, it is known that the endorsement agreement between a celebgram and an online shop is a form of service agreement that binds both parties under Indonesian civil law, as regulated in the Civil Code. In this agreement, the celebgram provides promotional services, while the online shop provides financial compensation. Endorsement agreements must comply with the same civil law principles as conventional agreements. Electronic messages that include the agreement are considered valid as written evidence. The principle of good faith (Article 1338 paragraph (3) of the Civil Code) is important in implementing agreements. Both parties must be honest and not hide information that could harm the other party. The application of this principle starts from the pre-agreement stage to the implementation of the agreement. Endorsement agreements made online via social media such as Instagram still have valid legal force if they fulfill the terms of the agreement according to applicable law.